Differential game theory with applications to missiles and autonomous systems guidance - Faruqi, Farhan A., 1944- (Aerospace series (Chichester, England), 2017)
Differential Game Theory with Applications to Missiles and Autonomous Systems explains the use of differential game theory in autonomous guidance and control systems. The book begins with an introduction to the basic principles before considering optimum control and game theory. Two-party and multi-party game theory and guidance are then covered and, finally, the theory is demonstrated through simulation examples and models and the simulation results are discussed. Recent developments in the area of guidance and autonomous systems are also presented. Key features: -Presents new developments and how they relate to established control systems knowledge.-Demonstrates the theory through simulation examples and models.-Covers two-party and multi-party game theory and guidance.-Accompanied by a website hosting MATLAB code. The book is essential reading for researchers and practitioners in the aerospace and defence industries as well as graduate students in aerospace engineering.